The Empowerment of Productive Zakat Influence on Independence of The Community - Hamzah Hamzah; Fifi Fata'tiatul Hidayah (International Journal of Nusantara Islam, 2019)
Empowerment through productive zakat is the effort of the Madina Zone of Dompet Dhuafa to create an independent society by developing business that utilize the potential of the community itself. Empowerment programs are needed by the community to be able to overcome economic in a sustainable manner. The majority of Indonesia’s population is Muslim, so one of the empowerment programs that is considered relevant is the empowerment through productive zakat as practiced by Madina Zone of Dompet Dhuafa. The empowerment of community is related to self-reliance. Self-reliance can be achieved through empowerment by involving participation from the community. The purpose of this research is to identify the influence of empowerment through a productive zakat carried out by Madina Zone on community self-reliance. The method used in this study is a quantitative approach supported by qualitative data. The location of this study was in the Jampang Village, Kemang District, Bogor Regency. The results of the study showed a significant level of empowerment in participation and a significant level of participation in self-relience.